2011
DOI: 10.1007/s10522-011-9350-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood group does not appear to affect longevity a pilot study in centenarians from Western Sicily

Abstract: Centenarians are the best example of extreme human longevity, and they represent a selected population in which the appearance of major age-related diseases, such as cancer, and cardiovascular diseases among others, has been consistently delayed or escaped. The study of the long-lived individual genetic profile has the purpose to possibly identify the genes and the allelic variations influencing extended life expectancy, hence considering them as biomarkers of age-related diseases onset and development. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Our study does not support the genetic association of ABO alleles with human longevity, as no statistical differences were found between centenarians and middle-aged controls even without multiple comparison correction, which is in agreement with the previous studies. 20,30 Our meta-analysis showed a consistent conclusion.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our study does not support the genetic association of ABO alleles with human longevity, as no statistical differences were found between centenarians and middle-aged controls even without multiple comparison correction, which is in agreement with the previous studies. 20,30 Our meta-analysis showed a consistent conclusion.…”
Section: Discussionsupporting
confidence: 79%
“…We carefully reviewed the studies that had previously reported a positive association between ABO blood groups and longevity. [15][16][17]20,30 As listed in Table 5, small sample size and statement for longevity are two common problems, which are critical influencers for population-based studies as the population is heterogeneous and stratified by many hidden or unnoticed factors. In this view, a larger population should produce a more robust statistical estimation.…”
Section: Discussionmentioning
confidence: 99%
“…distribution, since the prevalence of the B type in controls was approximately twice in the Japanese population than in our study. Another small pilot study, including 38 centenarians and 59 subjects aged 45-65 years from Sicily, showed that ABO blood group did not appear to be significantly related with longevity (16). Nevertheless, it cannot be ruled out that the limited number of centenarians enrolled in this previous investigation consistently attenuated the significance of the relationship between ABO blood type and survival.…”
Section: Letters To the Editormentioning
confidence: 77%
“…In a study carried out on a small sample of very long-lived Turkish population, no similar association was found [74]. Likewise, in a more recent study conducted in Sicilian centenarians, the ABO blood groups did not appear to affect longevity [75]. In a survey of 269 Japanese centenarians, B allele was found to be associated with longevity [76].…”
Section: Abo Blood Group and Evolutionmentioning
confidence: 88%